Pembuatan Kafein Salisilat Secara Semisintetis Dari Bubuk Kopi Olahan Tradisional Kerinci - Sestry Misfadhila; Zulharmita Zulharmita; Deni Hardian Siska (STIFARM Padang, 2016)
The caffeine contained in coffee powder processed traditionally taken in Kerinci can be isolated, crystallized and made into a caffeine salicylate. Isolation of caffeine conducted through the coffee powder with water extraction, fractionation with methylene chloride, and crystallized using acetone and petroleum ether. The crystallization process is obtained of caffeine powder which is then reacted with salicylic acid, caffeine salicylate formed by using the solvent toluene and petroleum ether. Identification of caffeine powder and caffeine salicylate include: organoleptic, melting range, color reaction, the ultraviolet spectrum, infrared spectrum and thin layer chromatography. The identification caffeine results meet the requirements listed in the Indonesian Pharmacopoeia V edition of 2014. The results of determining the wavelength of maximum absorption of caffeine powder isolation results was 276 nm, caffeine salicylate 243 & 307 nm. Rf values obtained from thin layer chromatography test for caffeine is 0.30 and caffeine salicylate 0.36.